The Influence of Zakat Institution Marketing, Public Awareness, and Self-Motivation on Zakat Mal Payment Compliance - Audira Luthfia Sungkar; Juliana Nasution; Muhammad Ikhsan Harahap (Islamic Economics and finance in Focus, 2026)
This study investigates the interplay between the marketing initiatives of zakat institutions, public awareness levels, and internal motivation regarding the compliance of paying zakat mal at the National Zakat Agency (BAZNAS) of Deli Serdang Regency. The research employs a quantitative causal associative approach. Data collection was executed by distributing questionnaires to 100 Muslim respondents in Deli Serdang with steady incomes, selected through purposive sampling. Statistical analysis was performed using multiple linear regression via SPSS software. The partial findings demonstrate that institutional marketing and public awareness exert a positive and significant influence on zakat compliance, with public awareness emerging as the most dominant factor. Conversely, the internal motivation variable exhibits a negative and significant effect due to a cultural anomaly, where high spiritual fervor paradoxically triggers a preference for distributing zakat directly to recipients rather than through formal channels. Simultaneously, institutional marketing, awareness, and internal motivation significantly impact compliance, explaining 63.8% of the data variance (Adjusted R Square 0.638), while the remainder is influenced by factors external to this research model.,